GPR124 regulates microtubule assembly, mitotic progression, and glioblastoma cell proliferation. Issue 8 (6th May 2019) - Cherry, Allison E.; Vicente, Juan Jesus; Xu, Cong; Morrison, Richard S.; Ong, Shao‐En; Wordeman, Linda; Stella, Nephi
Abstract: GPR124 is involved in embryonic development and remains expressed by select organs. The importance of GPR124 during development suggests that its aberrant expression might participate in tumor growth. Here we show that both increases and decreases in GPR124 expression in glioblastoma cells reduce cell proliferation by differentially altering the duration mitotic progression. Using mass spectrometry‐based proteomics, we discovered that GPR124 interacts with ch‐TOG, a known regulator of both microtubule (MT)‐plus‐end assembly and mitotic progression. Accordingly, changes in GPR124 expression and ch‐TOG similarly affect MT assembly measured by real‐time microscopy in cells. Our study describes a novel molecular interaction involving GPR124 and ch‐TOG at the plasma membrane that controls glioblastoma cell proliferation by modifying MT assembly rates and controlling the progression of distinct phases of mitosis. Main Points: Average expressions of GPR124 and ch‐TOG and MT assembly rates in glioblastomas allow normal prometaphase timing. Increased expression of GPR124 in glioblastomas leads to increased ch‐TOG expression and MT assembly rates and longer prometaphase. Reduced GPR124 expression in glioblastomas does not affect ch‐TOG expression and yet increase MT assembly rates by shortening prometaphase.